Down-regulation of protease activated receptor 2, interleukin-17 and other pro-inflammatory genes by subantimicrobial doxycycline dose in a rat periodontitis model - Castro, Myrella L.; Franco, Gilson C N; Branco-de-Almeida, Luciana S.; Anbinder, Ana L. [UNESP]; Cogo-Müller, Karina; Cortelli, Sheila C.; Duarte, Simone; Saxena, Deepak; Rosalen, Pedro L. (Journal of Periodontology, 2015)
Subantimicrobial dose doxycycline (SDD) has been used as an adjunct in periodontal treatment due to its matrix metalloproteinase inhibition properties. Although the benefits of SDD therapy, such as improvement in the parameters of periodontal probing depth and clinical attachment level, have been proven in multiple clinical studies, the comprehension of other biological mechanisms of action on periodontitis remains poorly investigated. Therefore, this animal model study evaluated the effects of SDD monotherapy on the expressions of the following key pro-inflammatory genes: Proteinase-Actived Receptor-2 (PAR2), Tumor Necrosis Factor alpha (TNF-α), Interleukin-17 (IL-17), and. IL-1β. Male Wistar rats were randomly assigned to: A) Control group: no ligature-induced periodontitis and no treatment; B) Ligature group: ligature-induced periodontitis and placebo treatment and C) Ligature + doxycycline group: ligature-induced periodontitis and SDD treatment. After the experimental time, animals were sacrificed and Reverse Transcriptase-Polymerase Chain Reaction was performed to analyze the mRNA expression of IL-1β, IL-17, TNF-α, and PAR2 in gingival tissue samples. Histological analyses were performed on the furcation region and mesial gingiva of mandibular first molars to measure periodontal bone loss and collagen content. SDD administration significantly downregulated PAR2, IL-17, TNF-α, and IL-1β mRNA expressions (p<0.05). In addition, SDD treatment was accompanied by lower rates of alveolar bone loss (p<0.05) and by maintenance of the amount of gingival collagen fibers. These findings reveal new perspectives regarding SDD efficacy since it can be partially related to pro-inflammatory gene expression modulation, even considering PAR2 and IL-17, which has not been investigated thus far.
Keywords: Alveolar bone loss; Doxycycline; Par-2; Periodontal diseases; Receptor